'A small leap for disabled man': the athlete-led evolution of the sports wheelchair and adaptive sports. Issue 1 (2nd January 2023) - Brady, Samuel
ABSTRACT: The history of the sporting wheelchair demonstrates that wheelchair athletes and non-disabled medical professionals – two distinct social groups as defined by the Social Construction of Technology – held different interpretations of wheelchair sport and technology, and their purpose. Originating as a form of rehabilitation, wheelchairs and wheelchair sport were once interpreted solely within the medical realm, resulting in restricted technical development for sporting wheelchairs due to concerns around user safety. Wheelchair athletes, however, adapted their equipment in resistance of medicalised rules, based on their reinterpretation of the technology and desire to advance wheelchair-based sports beyond the institution, legitimising technical innovation as a site of agency for disabled athletes. In doing so, the functionality and form of wheelchairs evolved, facilitating the creation of specialised, sport-specific wheelchairs, such as the basketball wheelchair and racing wheelchair. In response to this, the rules of these sports were altered, stabilising the athletes' interpretation of wheelchair technology as sporting devices, and wheelchair sport as elite competition.